Electron Probe Microanalysis Through Coated Oxidized Surfaces. (October 2019) - Matthews, Mike B.; Buse, Ben; Kearns, Stuart L.
Abstract: Low voltage electron probe microanalysis (EPMA) of metals can be complicated by the presence of a surface oxide. If a conductive coating is applied, analysis becomes one of a three-layer structure. A method is presented which allows for the coating and oxide thicknesses and the substrate intensities to be determined. By restricting the range of coating and oxide thicknesses, t c and t o respectively, x-ray intensities can be parameterized using a combination of linear functions of t c and t o . t c can be determined from the coating element k -ratio independently of the oxide thickness. t o can then be derived from the O k -ratio and t c . From t c and t o the intensity components of the k -ratios from the oxide layer and substrate can each be derived. Modeled results are presented for an Ag on Bi2 O3 on Bi system, with t c and t o each ranging from 5 to 20 nm, for voltages of 5–20 kV. The method is tested against experimental measurements of Ag- or C-coated samples of polished Bi samples which have been allowed to naturally oxidize. Oxide thicknesses determined both before and after coating with Ag or C are consistent. Predicted Bi M α k -ratios also show good agreement with EPMA-measured values.